O diário de classe e a cultura material escolar do curso técnico regular em mecânica da Escola Técnica Federal de São Paulo (1986-1989) - Brito, Alba Fernanda Oliveira (2016)
This research presents an analysis on the use of the class record book at Escola Técnica Federal de São Paulo (São Paulo Technical School - ETFSP), an Autonomous Entity Education Establishment, originally arising from the Escola de Aprendizes Artífices (School of Apprentices and Artifices - EAA) which, for almost forty years (1959-1998), formed Secondary Education technicians in the Capital City of São Paulo, in order to meet the Brazilian Industrial Market at that period. After several renewals and names, it is currently called Instituto Federal de Educação, Ciência e Tecnologia de São Paulo (São Paulo Federal Institute of Education, Science and Technology - IFSP). The main document sources are sets of class record books filled out by professors who ministered technical (specific) and general culture (propedeutics) classes at the Mechanics Regular Course of ETFSP between 1986 and 1989. Aiming at investigating the relationship between the class record books and the school material culture and its ordinary writing with reflections and development of the teaching practice, a qualitative research is made, centered in the analysis methodology of the contents registered. The theories in which the research are based on have support from teaching practice studies, documents and school archives inserted in the school material culture field. In that direction, the investigation relevance is also related to the fact that it historically discusses not only the document itself by also its uses and needs. The results obtained in the research indicate that the class record book it is not seen by the individuals involved as a support, reflection and teaching practice development tool, but as a procedural document for the description of tasks undertaken in the classroom, solidifying the culture of bureaucratic documents and inspection of the teaching work, even though ETFSP considers it a support tool for pedagogical activities